Live-Streaming Subscriber on Esport Professional Player: Expertise, Parasocial, and Streamer Attachment Factor To Getting the Subscribers - Primadana, Ligasyah Arnanda; Windasari, Nila Armelia (Journal of Business Management Education (JBME), 2023)
The advancing development of the internet creates new possibilities for new kinds of entertainment. The new entertainment is live-streaming unique content. However, there is still a lack of research on every variable in this phenomenon. There is a need for more research about certain variables in this context for a future new marketing method in a real-time platform. This paper explored the relationship between expertise, parasocial, attachment, and subscribe intention. The primary purpose of this research is to explore the variable relationship to achieve a specific framework for future research—the analysis uses partial least square (PLS-SEM) Analysis. The result is that expertise is the only significant relationship between all variables in subscribe intention. The limitation of this research is that it still uses an adaptation of measurement items with various topics such as social media, celebrities, and promotion. Future research about live-streaming needs to develop their measurement item to get more specific relationship models.